Radical and conservative operation in some liver hydatid cysts. Behavior with the adventitia - Perdomo, Roberto; Ferreira, Ciro; Alvarez, Carmelo (Cirugía del Uruguay, 1996)
In evolutíonary hydatíc cysts of the líver the adventítía acquíres physícal features such as sc/erotíc thíckeníng and ca/cífícatíon whích turns ít prone to ínfectíon and ínfluence those surgíca/ procedures whích total/y or partíally abandon ít (partía! cystectomy).